No evidence of reduced capacity during highly demanding cognitive tasks in healthy older adults at electroencephalographic risk of cognitive impairment - Jorge Sigg-Alonso; Mauricio González-López; Eduardo Gonzalez-Moreira; Rodolfo Solís-Vivanco; Thalía Fernández (PLoS ONE, 2025)
Healthy older adults with excessive theta absolute power (AP) are considered at electroencephalographic risk of developing cognitive impairment 7 to 10 years later. Although this population may exhibit a normotypic cognitive state, as revealed by traditional neuropsychological assessment, less is known about their performance during tasks with high cognitive demand and whether the degree of excessive theta AP can be used to predict their performance, which was our objective. We compared the scores from highly demanding memory tasks (i.e., the Visual Short-Term Memory Binding Test (VSTMBT) and the Loewenstein-Acevedo Scale for Semantic Interference and Learning (LASSI-II)) between older adults with and without excessive theta AP. No significant differences were found between the groups for any test score or for the predictive value of the theta AP for performance. The results of this study provide evidence that older adults with excessive theta APs do not exhibit impaired performance in highly demanding cognitive contexts. The possible role of cognitive reserve in alleviating evidence of deterioration is discussed.